The Effect of Entrepreneurship Knowledge and Motivation on Business Successs through Self-Efficacy on MSMEs Activities in the City of Jember - Sapta Yanuar; Diana Sulianti K. Tobing; Ika Barokah Suryaningsih (Budapest International Research and Critics University, 2022)
The aims of the study are to find out the effect of entrepreneurship knowledge and motivation on business successs through self-efficacy on msmes activities in the city of jember. This study uses quantitative research Method. The result shows that Entrepreneurial knowledge and motivation had a direct effect on business successs by 0.343 and 0.419., Entrepreneurial knowledge had indirect effect on business success through self-efficacy by 0.011 so the total effect was 0,354. Motivation has an indirect effect on business success through self-efficacy by 0.062 so the total effect was 0,481.